Impact of COVID-19 pandemic on air quality changes in Shanghai, China. Issue 1 (4th March 2022) - Filonchyk, Mikalai; Yan, Haowen; Hurynovich, Volha; Wang, Zhuo
Abstract: The SARS-CoV-2 (Severe Acute Respiratory Syndrome-related Coronavirus 2) and its concomitant disease COVID-19 (Coronavirus Disease 2019), discovered at the end of December 2019, have spread around the world, becoming a global public health problem. To prevent the spread of COVID-19, the Chinese government took strict lockdown measures in early 2020 in many cities. The purpose of this study was to evaluate changes in air quality in Shanghai, China's most populous city during the lockdown. Lockdown measures led to a decrease in anthropogenic activity and a concomitant reduction in air pollutant emissions, which led to a temporary improvement in air quality. Mean daily concentrations of PM2.5, PM10, SO2 and NO2 during a 2-week portion of the lockdown period (24 January–6 February) were respectively reduced by −19.2%, −44.7%, −21.5% and −33.6% compared to the same period in 2019. Even with the decrease in PM2.5 and PM10 concentrations, they were still more than four times higher than the World Health Organization standards (10 μg/m 3 and 20 μg/m 3, respectively). This study provides data useful for evaluating existing environmental policy, as it showed how the control of pollution sources can affect air quality.